Designing Arguments for Academic, Public, and Professional Audiences - Marzluf, Phillip (Open textbook library., 2024)
This college-level textbook guides students through five different types of arguments: evaluations, responses, persuasive rhetorical arguments, proposals, and practical professional development arguments. Students are introduced to rhetorical concepts and strategies to enable them to more effectively appeal to different types of audiences. Students will gain practice in audience-based reasoning, basing their reasons and evidence on the assumptions, beliefs, and values of their readers.